Anticipated responses of early adopter genetic specialists and nongenetic specialists to unsolicited genomic secondary findings. (October 2018) - Christensen, Kurt; Bernhardt, Barbara; Jarvik, Gail; Hindorff, Lucia; Ou, Jeffrey; Biswas, Sawona; Powell, Bradford; Grundmeier, Robert; Machini, Kalotina; Karavite, Dean; Pennington, Jeffrey; Krantz, Ian; et al.
Abstract Purpose Secondary findings from genomic sequencing are becoming more common. We compared how health-care providers with and without specialized genetics training anticipated responding to different types of secondary findings. Methods Providers with genomic sequencing experience reviewed five secondary-findings reports and reported attitudes and potential clinical follow-up. Analyses compared genetic specialists and physicians without specialized genetics training, and examined how responses varied by secondary finding. Results Genetic specialists scored higher than other providers on four-point scales assessing understandings of reports (3.89 vs. 3.42, p = 0.0002), and lower on scales assessing reporting obligations (2.60 vs. 3.51, p < 0.0001) and burdens of responding (1.73 vs. 2.70, p < 0.0001). Nearly all attitudes differed between findings, although genetic specialists were more likely to assert that laboratories had no obligations when findings had less-established actionability (p < 0.0001 in interaction tests). The importance of reviewing personal and family histories, documenting findings, learning more about the variant, and recommending familial discussions also varied according to finding (allp < 0.0001). Conclusion Genetic specialists felt better prepared to respond to secondary findings than providers without specialized genetics training, but perceived fewer obligations for laboratories to report them, and the two groups anticipated similar clinical responses. Findings may inform development of targeted education and support.